Increase in glucose transporter densities of Glut3 and decrease of glucose utilization in rat brain after one week of hypoglycemia - Duelli, Roman; Staudt, Richard Erhard; Dümbgen, Lutz; Kuschinsky, Wolfgang (Brain research, 1999)
The present study addresses the question whether a chronic decrease of plasma glucose concentration for 1 week induces a global or local increase in glucose transporter densities Glut1 and Glut3 in the brain. To induce chronic hypoglycemia insulin was infused into rats by osmotic minipumps for 1 week resulting in a mean plasma glucose concentration of 3.1±0.5 mmol/l (control group: 8.1±0.5 mmol/l). Global and local densities of Glut1 and Glut3 glucose transporters were measured by immunoautoradiographic methods. The mean density of glucose transporters Glut1 remained unchanged, whereas the mean density of Glut3 increased slightly, although significantly. To determine whether the increased density of Glut3 is related to a change in glucose metabolism, the local cerebral metabolic rate of glucose (lCMRglc) was quantified by the 2-deoxyglucose method. Mean glucose utilization was decreased by 15%. Local analysis of transporter densities (Glut1 and Glut3) and glucose utilization showed a significant correlation between local glucose transporter densities (Glut1 and Glut3) and lCMRglc during hypoglycemia as already previously observed during normoglycemia. It is concluded that 1 week of hypoglycemia is a stimulus for the induction of additional glucose transporters Glut3 in the brain. These additional neuronal glucose transporters may support the maintenance of glucose utilization which is not completely maintained under these conditions.